(untitled) (International Journal of Health, Animal Science and Food Safety, 2014)
Two different products of vacuum packed cold smoked herrings were analyzed at time intervals in order to evaluate the efficiency of the processing and product stability. Microbiological total counts, lactic acid bacteria, total coliforms, pH, water activity, water content, salt content (WPS) were determined. Differences in hygienic conditions and salt content were found. Principal components analysis (PCA) of volatile compounds determined by GC-MS analysis allowed the differentiation of the processing.